A Mixture of Functional Complex Extracts from Lycium barbarum and Grape Seed Enhances Immunity Synergistically In Vitro and In Vivo. Issue 6 (23rd May 2019) - You, Jiaqi; Chang, Yaning; Zhao, Di; Zhuang, Jiafeng; Zhuang, Wei
Abstract : Abstract: A mixture of multiple ingredients is often more effective than the individual ingredients. The functions of Lycium barbarum polysaccharide (LBP) glycoconjugate and grape seed procyanidins (GSP) are widely known. Here, we investigated the synergistic immune‐enhancing activity of LBP and GSP. Atomic force microscopy results suggested that the mixture of LBP and GSP exhibited circular structure unlike LBP alone, and the addition of polyphenols may change the spatial conformation of the sugar chain. The changes in the structure were related to the synergistic effect of the two functional agents on immune recovery. In vitro, the proliferation rate of splenocytes was higher in LBP + GSP group (64.16%), rather than the sum of LBP group (13.01%) and GSP group (43.61%) individually used. This synergistical proliferation of splenocytes may be correlated to the increasing intracellular free calcium levels. Furthermore, the mixture significantly enhanced the immunity in vivo, as evident from the recovery of peripheral white blood cell counts in LBP + GSP group (18.535 × 10 9 /L) to normal group levels (18.115 × 10 9 /L) and higher B cell proliferation than normal group ( P < 0.05). These results highlight the immune‐enhancing activity of the combination of LBP and GSP associated with the structural changes, which may facilitate the development of functional foods with fewer resources but enhanced activities. Practical Application: The synergistic effects of LBP and GSP on immunomodulatory were better than the sum of the effects of the individual agents both in vitro and in vivo . Our results may provide a research‐based support for the development of related functional products and an insight into the production of food resources with a fewer but more effective functional agents for better results.